Pemberdayaan Masyarakat dalam Pengolahan Ikan Cakalang (Katsuwonus pelamis) Menjadi Produk Unggulan Bernilai Ekonomis untuk Masyarakat Pesisir - Lukum, Astin; Pikoli, Masrid (Jurnal Sibermas (Sinergi Pemberdayaan Masyarakat), 2022)
East Lobuto village is one of the villages in Biluhu Subdistrict. Most of the people's livelihoods are fishermen. The development of various processed products from fisheries can be used as an alternative to growing fish consumption habits for the community, as well as an effort to increase the nutritional value of the community. One form of the processed fish product is fish meatballs. Meatballs are processed products from meat that are quite popular with the public. In general, meatballs are made from beef, but lately many are found in the meatball market made from fish meat. The type of fish that will be used for meatball making materials is cakalang fish.